2011
DOI: 10.1121/1.3621445
|View full text |Cite
|
Sign up to set email alerts
|

Detection and rate discrimination of amplitude modulation in electrical hearing

Abstract: Three experiments were designed to examine temporal envelope processing by cochlear implant (CI) listeners. In experiment 1, the hypothesis that listeners' modulation sensitivity would in part determine their ability to discriminate between temporal modulation rates was examined. Temporal modulation transfer functions (TMTFs) obtained in an amplitude modulation detection (AMD) task were compared to threshold functions obtained in an amplitude modulation rate discrimination (AMRD) task. Statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 37 publications
11
57
1
Order By: Relevance
“…The AMDTs were generally worse with this method, but controlling for loudness cues did not affect the general finding that AMDTs became worse when the modulation frequency increased. In another study with five CI users, Chatterjee and Oberzut (2011) found that there was a small but significant effect of roving (without loudness balancing) on the overall gain of the TMTF. The shape of the TMTF, however, was unaffected.…”
Section: Further Considerationsmentioning
confidence: 94%
See 1 more Smart Citation
“…The AMDTs were generally worse with this method, but controlling for loudness cues did not affect the general finding that AMDTs became worse when the modulation frequency increased. In another study with five CI users, Chatterjee and Oberzut (2011) found that there was a small but significant effect of roving (without loudness balancing) on the overall gain of the TMTF. The shape of the TMTF, however, was unaffected.…”
Section: Further Considerationsmentioning
confidence: 94%
“…This task would be very difficult for the prelingually deafened CI users, especially for the low modulation frequencies, where changes in loudness are clearly noticeable during the stimulus. However, when no balancing is performed, an even larger amount of roving should be applied to correct for possible loudness cues, especially when modulation depths are larger than −15.92 dB re 100%, which is >16% (Chatterjee & Oberzut 2011). The latter occurs for most of the modulation frequencies of the prelingually deafened CI users (Fig.…”
Section: Further Considerationsmentioning
confidence: 97%
“…For an n-channel vocoder, the speech signal was bandpass filtered into n logarithmically spaced bands (24 dB/octave) following the Greenwood frequency-place map. The time-varying speech envelope from each band was extracted using half-wave rectification and low-pass filtering (24 dB/oct filter, 160 Hz cutoff: the 160 Hz cutoff frequency was chosen to approximate the envelope discrimination abilities of the average CI listener (e.g., Chatterjee & Peng, 2008; Chatterjee & Oberzut, 2011)). The envelope derived from each band was used to modulate a band-pass filtered white noise with the same filter parameters, center frequency and bandwidth.…”
Section: Methodsmentioning
confidence: 99%
“…Psychophysical studies in humans are in agreement that sensitivity to modulation degrades with decreasing level of stimulation (Chatterjee and Robert, 2001;Fu, 2002;Galvin and Fu, 2005;Pfingst et al, 2007;Galvin and Fu, 2009;Chatterjee and Oberzut, 2011;Fraser and McKay, 2012), although a study using animals (Middlebrooks, 2008) has shown the opposite effect. Data from Fraser and McKay (2012) showed that, when loudness cues were well controlled, temporal modulation transfer functions demonstrated a low-pass characteristic with a cut-off frequency similar to normal hearing listeners at sufficiently loud levels, deteriorating with lower stimulus levels.…”
Section: Discussionmentioning
confidence: 78%